Generation of the human iPSC line ESi132-A from a patient with retinitis pigmentosa caused by a mutation in the PRPF31 gene - Estefanía Caballano Infantes; Laurie Clauzon; Berta de la Cerda Haynes; Francisco Díaz-Corrales (Stem Cell Research)
Mutations in the PRPF31 gene are a well-known cause of autosomal dominant retinitis pigmentosa (RP), the most prevalent genetic form of blindness in adults, affecting 1 in 4,000 individuals globally. In this study, peripheral blood mononuclear cells from a patient carrying a heterozygous mutation in PRPF31 were reprogrammed to generate the human iPSC line ESi132-A. This cell line was thoroughly characterized for self-renewal and pluripotency. These cells will be used to develop advanced 3D biomodels based on multi-ocular cell differentiation to assess the efficacy of novel treatments for RP including innovative drug and gene therapies.